A Review of the Effect of Electric Discharge Machining on the Surface Integrity of Metallic Parts - Mehmood, S.; Anjum, N. A.; Anwar, W.; Rahman, R. A.; Javed, K.; Badshah, S. (The Nucleus, 2018)
In Electric Discharge Machining (EDM), after each electric discharge, a small portion of the molten pool is removed and the residue re-solidifies on the surface in the form of layer. This re-solidified layer has different microstructure and metallurgical properties than the parent material. Many investigations have been carried out on EDM of different materials to evaluate the influence of electrical parameters, dielectric type, electrode material and discharge gap on the Material Removal Rate (MRR), tool wear rate and surface integrity (surface roughness, cracks, residual stresses and white layer formation). Voltage, pulse current, pulse on-time, pulse off-time and polarity are electric parameters that control discharge energy as well as heating and cooling times. It has been observed that high discharge energy gives high surface roughness, high MRR and high residual stresses. A detailed literature review comprising effects of different parameters on surface conditions like metallurgical characteristics, surface roughness, surface hardness and distribution of residual stresses, is presented here